Peran Fintech dalam Meningkatkan Inklusi Keuangan Gen-Z - Nurdjanna Fadjrin Uluputty; Andi Hidayat; Nurwahyu Ningsih; Yurike Virginia Anggun; Reski Salim (Management and Accounting Research Journal, 2025)
This study aims to analyze the influence of financial technology (fintech) on the financial inclusion of Generation Z in Indonesia. The research method used was quantitative with an online survey approach via Google Forms. Data were collected from 83 Generation Z respondents and analyzed using simple linear regression with the help of SPSS version 21. The results showed that fintech had a positive and significant effect on the financial inclusion of Generation Z. The more often Generation Z uses fintech services, the higher their level of financial inclusion. This study also highlights the gap in financial inclusion between urban and rural Generation Z. Therefore, efforts are needed to increase the financial inclusion of rural Generation Z, including by improving access to technological infrastructure and financial literacy